Exploration of Novel Lipase from Plant Seeds and Plant Latexes - Istyami, Astri Nur; Sari, Myra Wardati; Gultom, Cristy Hagi; Prakoso, Tirto; Soerawidjaja, Tatang Hernas (Indonesian Journal of Chemical Research, 2024)
As the demand for fatty acids increases, the enzymatic process of triglyceride hydrolysis emerges as a promising technology. Compared to microbial lipase, utilization of plant lipase is more practical due to its ease of preparation and cost-efficiency. This work aimed to verify the degree of lipolysis of several novel lipase sources from plants. Novel lipase sources investigated were seeds of kapok (Ceiba pentandra), java almond (Sterculia foetida), pongam (Milletia pinnata), sea mango (Cerbera manghas), tamanu (Calophyllum inophyllum), latex of sea mango, aveloz (Euphorbia tirucalli), and jackfruit (Artocarpus heterophyllus). Several acknowledged plant lipase sources were also compared, i.e. seeds of castor bean (Ricinus communis), physic nut (Jatropha curcas), rice bran (Oryza sativa), latex of frangipani (Plumeria rubra) and papaya (Carica papaya). Plant lipase was utilized in the hydrolysis of olive oil at room temperature. Results for seed and latex lipase were compared and technical issues were reported. Several plant lipases are remarkably active and potential to compete with microorganism lipases in industrial applications.